An online app platform enhances collaborative medical student group learning and classroom management. (1st February 2016) - Peacock, Justin G.; Grande, Joseph P.
Abstract: Purpose : The authors presented their results in effectively using a free and widely-accessible online app platform to manage and teach a first-year pathology course at Mayo Medical School. Methods used : The authors utilized the Google "Blogger", "Forms", "Flubaroo", "Sheets", "Docs", and "Slides" apps to effectively build a collaborative classroom teaching and management system. Students were surveyed on the use of the app platform in the classroom, and 44 (94%) students responded. Results : Thirty-two (73%) of the students reported that "Blogger" was an effective place for online discussion of pathology topics and questions. 43 (98%) of the students reported that the "Forms/Flubaroo" grade-reporting system was helpful. 40 (91%) of the students used the remote, collaborative features of "Slides" to create team-based learning presentations, and 39 (89%) of the students found those collaborative features helpful. "Docs" helped teaching assistants to collaboratively create study guides or grading rubrics. Overall, 41 (93%) of the students found that the app platform was helpful in establishing a collaborative, online classroom environment. Conclusions : The online app platform allowed faculty to build an efficient and effective classroom teaching and management system. The ease of accessibility and opportunity for collaboration allowed for collaborative learning, grading, and teaching.